Conceptualizing the de–materializing characteristics of internal inclusion in crowdsourced open strategy. Issue 5 (October 2020) - Mount, Matthew P.; Clegg, Stewart R.; Pitsis, Tyrone S.
Abstract: The increasing ubiquity of interactive technologies such as crowdsourcing is one of the major forces underpinning the emerging concept of open strategy. The large-scale interactive functionality afforded by such technologies offers unparalleled possibilities for including actors across the entire organization in co-creative efforts to respond to strategic issues or shape the organization's strategy. However, the ability of all organizational actors to engage in the production and co-development of strategy ideas, which together constitute inclusion in open strategy, is hindered by the highly politicized, often secretive and organizationally complex arena through which strategy unfolds. In this conceptual paper, we address this issue by drawing on the strategy tools-in-use framework to explore the material characteristics of crowdsourcing that de-materialize the material barriers to inclusion in open strategy. Drawing on the information systems literature, we argue that characteristics of anonymity, parallelism, group memory, process structuring and information processing are important material enablers of inclusion in open strategy.